First Report of Diaporthe eres Causing Leaf Spot on Pseudocydonia sinensis in China - Zhang, Qiao-Qiao (Plant disease, 2022)
Pseudocydonia sinensis is a Chinese ornamental plant with great landscaping value. Its fruit is additionally used for medicinal purposes (Lim 2012). In June 2020, a leaf spot disease was observed in the campus of Nanjing Forestry University (32°04'34.53″N 118°48'42.06″E). The symptoms began with irregular red-brown spots, which gradually enlarged, extended and overlapped, with an incidence of 85% (29/34 trees). Pieces of leaf tissue (3 to 4 mm²) from the lesion margins were surface-sterilized with 75% ethanol for 30 s and 1% NaClO for 90 s. Subsequently, the tissues were rinsed with sterile H2O, placed on potato dextrose agar (PDA) medium and incubated at 25℃ for 5 days. The same fungus was isolated from 90% of tissues. Pure cultures were obtained by monosporic isolation.The representative isolate NJMG 5-7 was used for morphological and molecular characterization. The growing fungal colony on PDA was initially white, but gradually turned grey. Pycnidia formation was observed on PDA supplemented with alfalfa stems. The pycnidia produced two different types of conidia, α and β, which ooze out in yellow creamy mucilaginous masses. Conidiophores were hyaline, cylindrical and smooth, 16.8 to 33.1 × 1.5 to 2.6 μm (n=30). Conidiogenous cells were 13.6 to 29.3 × 1.5 to 2.7 μm (n=30). The α-conidia were, unicellular, hyaline elliptical or fusiform, bi-guttulate, 6.5 to 9.2 × 1.8 to 3.3 µm (n = 50). The β-conidia were hyaline, aseptate, without guttules, filiform, curved, with obtuse ends, 12.5 to 25 × 1.0 to 1.8 µm (n = 50). To verify species identity, the partial sequences of the internal transcribed spacer (ITS) region, and calmodulin (CAL), translation elongation factor 1 alpha (EF1-a), and beta-tubulin genes (TUB) were amplified from isolate NJMG 5-7 with primers ITS1/ITS4 (White et al. 1990), CAL-228F/CAL-737R (Carbone & Kohn 1999), EF1-728F/EF1-986R (Carbone and Kohn 1999), and Bt2a/Bt2b (Glass and Donaldson 1995), respectively. The sequences were deposited in GenBank (OP223050 for ITS, OP252809 for CAL, OP252807 for EF1-a, and OP252808 for TUB). A BLAST search of GenBank showed that ITS, CAL, EF1-a and TUB sequences of NJMG 5-7 were similar to those of D. eres CBS 138594 (99% identity), AR5193 (99%), AR5193 (99%) and MG281193 (100%), respectively. The morphological and molecular results identified the isolate as D. eres (Feng et al. 2015). To fulfill Koch's postulates, a pathogenicity test was conducted using three P. sinensis plants. Six leaves from each tree were wounded and inoculated with mycelial plugs (about 4 mm in diameter) of D. eres from a 3-day-old culture grown on PDA. Inoculations with sterile PDA plugs on different leaves of the same tree were used as controls. All inoculated leaves were enclosed in plastic bags together with a wet cotton ball inside. Sterile H2O was sprayed into the plastic bags to keep moisture conditions. Five days later, all inoculated points showed lesions similar to those previously observed in the field, whereas controls were asymptomatic. The pathogen was successfully reisolated from the inoculated symptomatic parts on PDA and identified from its morphology, thus fulfilling Koch's postulates. This fungus can cause a variety of diseases. To our knowledge, this is the first report of D. eres causing leaf spots on P. sinensis in the world. These findings provide a foundation for future studies on the epidemiology and control of this newly emerging disease